EVALUATION OF TURF GRASS SPECIES SUITABLE FOR TROPICAL CONDITIONS BASED ON QUANTITATIVE AND QUALITATIVE TRAITS - UBENDRA,; M. JAWAHARLAL,; C. SUBESH RANJITH KUMAR, (The Bioscan, 2015)
Turf grasses play a vital role in enhancing quality of life in contemporary urban livelihood. Water quantity is the most important challenge worldwide in establishing and maintaining quality turf. The present study was aimed to investigate the performance of twelve native turfgrasses under tropical condition. Morphological, physiologi- cal parameters and visual quality (shoot color, shoot density and shoot uniformity) were also recorded. It was found that temperature has significant effect on the performance of turfgrasses. Bermuda grass which had the highest root length (41.59 cm), root density (8.08), dry weight of root (5.04), turf quality (8.53 / 9), total chlorophyll (1.24 mg g-1), relative water content (85.62 %) and stomatal index (upper) (26.94 %) was found to be most drought tolerant followed by Zoysia japonica which is best suitable for stress tolerant conditions.